2013
DOI: 10.1371/journal.pbio.1001676
|View full text |Cite
|
Sign up to set email alerts
|

PLZF Regulates Fibroblast Growth Factor Responsiveness and Maintenance of Neural Progenitors

Abstract: A transcription factor called Promyelocytic Leukemia Zinc Finger (PLZF) calibrates the balance between spinal cord progenitor maintenance and differentiation by enhancing their sensitivity to mitogens that are present in developing embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 85 publications
1
58
0
Order By: Relevance
“…PLZF is also expressed in dividing progenitors and downregulated during neural differentiation . In Drosophila, the PLZF ortholog tramtrack blocks neuronal differentiation and regulates glial development from neural progenitors .…”
Section: Stem Cell Self‐renewalmentioning
confidence: 99%
“…PLZF is also expressed in dividing progenitors and downregulated during neural differentiation . In Drosophila, the PLZF ortholog tramtrack blocks neuronal differentiation and regulates glial development from neural progenitors .…”
Section: Stem Cell Self‐renewalmentioning
confidence: 99%
“…Positioned within the C‐terminal region of PLZF, the nine C2H2 zinc finger motifs facilitate direct sequence‐specific DNA binding to target genes. Cell and signaling context dependent, PLZF can serve as a transcriptional activator or repressor (Fahnenstich et al, ; Gaber, Butler, & Novitch, ; Ikeda et al, ; Kommagani et al, ; Labbaye et al, ; Liu et al, ; Mao et al, ; Singh et al, ; Suliman et al, ; Szwarc et al, ; Wang et al, ). Given its pleiotropic effects, PLZF drives a broad spectrum of developmental processes and physiological responses, including limb skeletal patterning, innate immune cell development, hematopoiesis, and spermatogenesis; reviewed in Suliman et al ().…”
Section: Introductionmentioning
confidence: 99%
“…The Plzf KO mouse exhibits homeotic‐like anterior‐to‐posterior transformations in the axial and appendicular skeleton, causing hindlimb abnormalities such as fused or extra digits, loss of the tibia or conversion of the fibula to a tibia‐like structure, and kinked tails (Barna et al, ). Subsequent analysis also revealed that these mutant mice exhibit impairments in the development of hematopoietic stem cell and neural progenitors (Gaber et al, ; Vincent‐Fabert et al, ), in spermatogonial self‐renewal (Buaas et al, ; Costoya et al, ), and in development of innate‐like features of invariant natural killer T (iNKT) cells (Kovalovsky et al, ; Savage et al, ; Savage, Constantinides, & Bendelac, ; Xu et al, ). Important from a translational perspective, many of these phenotypes also arise in humans with loss‐of‐function PLZF mutations (Fischer et al, ), highlighting the evolutionary conserved role of PLZF.…”
Section: Introductionmentioning
confidence: 99%
“…These data could be explained by the heterogeneity of reprogrammed BSKM LT hiNSCs, which represent distinct regional identities and developmental stages of NSCs. Despite the heterogeneous identity of BSKM LT hiNSCs, all BSKM LT hiNSC lines from distinct origins were negative for PLZF, a transcription factor that functions in early neurodevelopment and disappears in the late stage of neurodevelopment (35), supporting that BSKM LT hiNSCs more likely represent late-stage radial glial cells in developing brain (Fig. 1D, Supplementary Fig.…”
Section: Robust and Reproducible Generation Of Hinscsmentioning
confidence: 77%